1997
DOI: 10.1161/01.cir.96.4.1282
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l -Arginine Reduces the Progression of Atherosclerosis in Cholesterol-Fed Rabbits

Abstract: Dietary L-arginine improves NO-dependent vasodilator function in cholesterol-fed rabbits and completely blocks the progression of plaques via restoration of NO synthase substrate availability and reduction of vascular oxidative stress. Lovastatin treatment has a weaker inhibitory effect on the progression of atherosclerosis and no effect on vascular NO elaboration, which may be due to its stimulatory effect on vascular superoxide radical generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
1
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(129 citation statements)
references
References 40 publications
9
115
1
4
Order By: Relevance
“…Besides its vasodilatory effects, NO has many reported antiatherogenic properties, including reducing platelet aggregability [40] , limiting vascular smooth muscle cell proliferation [41] , inhibiting adhesion molecule expression in endothelium [42] , inhibiting neutrophil and monocyte adhesion to the endothelium [43,44] , and preventing monocyte chemotaxis [45] . Chronic provision of L-arginine to the diets of hypercholesterolemic rabbits has been reported to improve endothelium-dependent vasodilation and reduce the extent of atherosclerotic lesions [46] . Also contributive to hyperlipidemia-mediated endothelial dysfunction is the increased production of reactive oxygen species (ROS, such as superoxide anion) and resultant abundance of reaction product peroxynitrite [37] .…”
Section: Vascular Dysfunction In Metabolic Syndrome (Hyper Lipidemia mentioning
confidence: 99%
“…Besides its vasodilatory effects, NO has many reported antiatherogenic properties, including reducing platelet aggregability [40] , limiting vascular smooth muscle cell proliferation [41] , inhibiting adhesion molecule expression in endothelium [42] , inhibiting neutrophil and monocyte adhesion to the endothelium [43,44] , and preventing monocyte chemotaxis [45] . Chronic provision of L-arginine to the diets of hypercholesterolemic rabbits has been reported to improve endothelium-dependent vasodilation and reduce the extent of atherosclerotic lesions [46] . Also contributive to hyperlipidemia-mediated endothelial dysfunction is the increased production of reactive oxygen species (ROS, such as superoxide anion) and resultant abundance of reaction product peroxynitrite [37] .…”
Section: Vascular Dysfunction In Metabolic Syndrome (Hyper Lipidemia mentioning
confidence: 99%
“…(24)x. A reduction of NO synthesis predisposes to atherosclerosis (25). Oral administration of L-arginine has a protective effect with respect to plaque formation (18).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of plasma ADMA concentration has also been seen in response to probucol in rats [65]. In contrast, administration of L-arginine, the key substrate for NO synthase in the biosynthesis of NO, does not alter ADMA concentration but increased the L-arginine to ADMA ratio resulting in improved endothelium-dependent vasodilatation in animals and humans [38,49,50]. Of note, patients with unstable angina and reduced endothelium-dependent coronary vasodilatation had markedly improved anginal symptoms after 6 months of therapy with L-arginine (9 g/day) [66].…”
Section: Therapeutic Modulation Of Adma Concentrationsmentioning
confidence: 99%
“…It has been shown that by increasing plasma homocysteine concentrations using methionine infusion, FMD is impaired and this is associated with increased plasma ADMA [33]. Increased plasma concentrations of ADMA have also been described in a number of other conditions (Tables 1, 2) including diabetes mellitus, hypercholesterolaemia, hypertriglyceridaemia, hypertension, preeclampsia, stroke, peripheral vascular disease, congestive heart failure and acute coronary events [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. Of interest, increased ADMA concentrations have also been implicated in the pathogenesis of conditions not affecting the cardiovascular system such as schizophrenia although the exact mechanism has yet to be clarified [55].…”
Section: Adma and Endothelial Dysfunction In Disease Statesmentioning
confidence: 99%